Effect of oxytocin on parturition in sows - G H Kiracofe; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1969)
The hormone oxytocin (a hypothalamic neurosecretion that is stored in the posterior pituitary gland) stimulates' uterine contractions during natural parturition. Commerical oxytocin has been used to induce labor or to intensify uterine contractions during difficult or prolonged labor in sows. This test evaluated use of one level of a commercial oxytocin during normal parturition.; Swine Day, Manhattan, KS, September 25, 1969
Keywords: Swine day; 1969; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 151; Swine; Neurosecretion; Oxytocin